Applications of artificial intelligence in radiation protection. (4th August 2014) - Tan, C.L.; Pang, C.M.; Chant, Y.C.; Starkey, C.
This paper describes an expert system currently being developed for use in the Radiation Protection Inspectorate, under the Ministry of Health, Singapore. The initial phase aims at assisting the Inspectorate in providing advice upon public enquiries regarding radiation protection, licensing and other regulatory matters. Currently, the Inspectorate's scientific officers, who are fully conversant with the radiation protection legislation, have to handle frequent enquiries of this nature. The system will enable general clerical staff to answer such routine questions, as far as possible, without having to rely on scientific officers. The paper concludes with a discussion on future directions of this research.